EFEKTIVITAS PEMBELAJARAN KOOPERATIF MELALUI PROSES PEMBELAJARAN KIMIA PADA MATERI SISTEM KOLOID - Kamelia S, Susi (Universitas Islam Sumatera Utara, 2023)
This study aims to determine the effectiveness of cooperative learning in chemistry learning on colloidal system material. This study used a purposive sample population and sample by taking 2 classes in class xi ipa. This research method uses experimental research through pre-test and post-test testing as well as analytical tests through normality tests, homogeneity, and t tests. The results of the study show that through the pre-test, post-test both in control and experiment and also based on the results of the analysis test through the t test where the price of tcount ttable is 3.53 2.571 with a significance level (α = 0.05). The conclusion in this study is that the effectiveness of cooperative learning through the process of learning chemistry on colloidal system material can provide better learning outcomes for students than conventional learning thereby increasing learning creativity in chemistry students